2017
DOI: 10.1016/j.seppur.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A review of principles and applications of magnetic flocculation to separate ultrafine magnetic particles

Abstract: Liqun Luo, Anh V Nguyen / A review of principles and applications of magnetic flocculation and separation of ultrafine magnetic particles 2 H I G H L I G H T S • The principles of magnetic separation have been critically reviewed; • Both external and interparticle forces for ultrafine particles are reviewed and compared; • Suspensions stability of the particles factors are described and analyzed; • Various modeling of magnetic flocculation are introduced and some of the applications are illustrated. Liqun Luo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 75 publications
(155 reference statements)
0
18
0
2
Order By: Relevance
“…At acidic pH, the CS‐grafted MNPs are positively charged and adsorb to the negatively charged surface of emulsified oil droplets (about 2 µm) forming aggregates (about 100 µm) which then further grew by coming together through applying a magnetic field. More information on the synthesis and characterization of magnetic flocculants and their applications can be found elsewhere …”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
“…At acidic pH, the CS‐grafted MNPs are positively charged and adsorb to the negatively charged surface of emulsified oil droplets (about 2 µm) forming aggregates (about 100 µm) which then further grew by coming together through applying a magnetic field. More information on the synthesis and characterization of magnetic flocculants and their applications can be found elsewhere …”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
“…However, the increasing grinding fineness also results in the size drop of iron carbide particle. Fine particles cause the aggregation easily, which leads to the decrease of the iron recovery rate in magnetic separation [37]. When the size fraction continues to increase, both the iron content and iron recovery rate show downtrends, due to the enhanced particles aggregation.…”
Section: Influence Of Na 2 So 4 Dosagementioning
confidence: 99%
“…The first two ways are more closely related to magnetic field distribution of separation space and the latter one may be accomplished by changing the surface hydrophilic property of feebly magnetic minerals under the action of surfactants. Some basic research can be found on selective hydrophobic or magnetic flocculation [13][14][15][16][17]. However, complex procedures of forming suitable floccules make it difficult to hold steady running in the production of mineral processing.…”
Section: Introductionmentioning
confidence: 99%